INCREASING THE COMPETENCE OF HUMAN RESOURCES IN ORDER TO CREATE COMPETITIVENESS - Pandrianus Baillon; Tutik Winarsih (Transpublika Publisher, 2025)
Modern lifestyles have made appearance trends, including hairstyles, a staple of urban society. This has fuelled the growth of the barbershop industry, including Barbershop 99 located in East Surabaya. This study aims to identify the condition of human resource (HR) competencies, factors that influence their improvement, competency improvement strategies implemented by Barbershop 99, and their impact on business competitiveness. The research method used was a descriptive approach with data collection techniques through interviews and observations, involving all 30 employees of Barbershop 99 as informants. The results showed that HR competence at Barbershop 99 is quite good and contributes positively to increasing competitiveness. Competency improvement strategies are carried out through routine technical training, professional development, establishment of a collaborative work culture, mentoring system, and provision of incentives and career paths. This increase in competence has a direct impact on professionalism, work efficiency, harmonious relationships with customers, and high customer loyalty. The implications of these findings suggest that HR competencies are a strategic foundation in creating and maintaining competitive advantage. Therefore, it is recommended that the management of Barbershop 99 continue to update training materials, increase the frequency of coaching, and establish a sustainable competency evaluation system. In addition, the development of self-learning initiatives, mentoring among employees, and participation in professional events are recommended to strengthen Barbershop 99's position in the midst of competition in the modern service industry.